LAKU PANDAI WITHIN INSTITUTIONAL PILLARS: A QUALITATIVE STUDY ON FINANCIAL AGENTS IN RURAL COMMUNITIES - Paksi Mei Penggalih; Agustini Agustini; Zulfa Nur Auliatun Nissa’ (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
Rural communities still face limited financial access, so “Otoritas Jasa Keuangan (OJK)” established “Laku Pandai”. One of the banks implementing Laku Pandai is Bank BRI. Bank BRI's Laku Pandai is called “Agen BRILink” and “Mitra UMi”. This research aims to analyze how the meaning of “Laku Pandai” is seen from the three pillars of institutions (regulative, normative, cultural-cognitive). This research was conducted using descriptive qualitative approach with a purposive method. The selected informants were Agen BRILink” and “Mitra UMi” in Wonosobo Regency, consist of eight subdistricts. The data collection technique used in-depth interview with agents. The results of the research show that the existence agents play a crucial role in the regulation, norms, and understanding of financial services within the community. In the regulatory pillar, agents extend banking policies into local social spaces within a formal supervisory framework, although this also creates a hybridization between bank rules and local social practices. In the normative pillar, agents change perceptions of appropriate financial services within the local space, but their operations are influenced by norms of trust, privacy, and rural social proximity. Meanwhile, in the cultural-cognitive pillar, agents act as mediators of meaning, helping communities understand and normalize formal banking services until they become accepted practices and gain cognitive legitimacy. Overall, an agent's success is determined by its alignment with formal rules, social values, and the community's cultural understanding.